Utilization Of Intellectual Property Rights In Legal Protection Of Cultural Dance Arts - Prihatin, Lilik; Kusumaningsih, Mega Dwi (Jurnal Hukum dan Keadilan, 2024)
Copyright is regulated in Law Number 28 of 2014 concerning Copyright. Cultural dance arts are protected by Copyright, in accordance with Article 40 paragraph (1) of the Law. However, there are various complex barriers in protecting these cultural arts. The challenge of IPR is not only limited to legal protection, but also includes its utilization in protecting cultural dance arts. The research method used is normative juridical with data collection through literature study. The statutory approach in this study refers to IPR-related regulations, especially Law Number 28 of 2014 concerning Copyright. The results show two main aspects, namely the legal protection of IPR in cultural dance and the obstacles faced in its implementation. Although the existing legal protection framework is quite effective through copyright law, there are still weaknesses that need attention. The law has not fully elaborated on aspects of traditional cultural expressions, so further socialization efforts are needed regarding how dance art can also be treated with copyright protection as well as traditional cultural expressions. the unique characteristics of traditional cultural arts which are often oral and communal in nature are also an obstacle in the application of copyright. To overcome these obstacles, further efforts are needed in documenting cultural dance arts.